The effect of the integration of higher education into psychological regulation on the psychological state of college students - Peiqing Han, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The goal of this study is to examine the effect of integrating higher education into a psychological adjustment system on the psychological status of college students. The author randomly selected 500 college students from colleges and universities as the research objects. Psychological tests were carried out through the emotional regulation scale and symptom self-rating scale. Firstly, EpiData3.1 was used to input the data, and then the data was imported into SPSS22.0 for the reliability test and correlation analysis test. Finally, Amos22.0 was used to test the hypothesis model. The score of emotion regulation of college students is 57.20, and the average score of the total score of mental toughness is lower than 120. It shows that college students' overall mental toughness level is weak and needs improvement. The average mental health score is 147.96±53.29, which does not exceed 160 points. Higher education benefits students' physical form, function, and quality, but it also helps students' mood, shapes their will, and cultivates their personality.